2009
DOI: 10.1021/ic9006795
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorogenic, Nucleic Acid Directed “Click” Reaction

Abstract: A fluorogenic, nucleic acid directed, Cu(+)-catalyzed chemical reaction was developed that allows sequence-specific detection of nucleic acids at concentrations as low as 20 nM through monitoring of the increase of the fluorescence intensity. A single nucleotide mismatch in the template strand leads to the complete inhibition of this reaction. We observed that a Cu(+) ion stabilized with a water-soluble ligand is a significantly more efficient catalyst than free Cu(+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…Due to the spatial proximity of the reactive groups after hybridization, a chemical reaction is triggered, upon which, for example, a profluorophore is converted into a fluorophore. This technique allows for facile sensing of the hybridized oligonucleotide by means of fluorescence spectroscopy [7,8]. A similar principle was applied by Erben et al who reported a DNA templatetriggered, sequence-specific transfer of an aminoacyl group from one phosphorothioate modified PNA-peptide hybrid to another [9].…”
Section: Introductionmentioning
confidence: 91%
“…Due to the spatial proximity of the reactive groups after hybridization, a chemical reaction is triggered, upon which, for example, a profluorophore is converted into a fluorophore. This technique allows for facile sensing of the hybridized oligonucleotide by means of fluorescence spectroscopy [7,8]. A similar principle was applied by Erben et al who reported a DNA templatetriggered, sequence-specific transfer of an aminoacyl group from one phosphorothioate modified PNA-peptide hybrid to another [9].…”
Section: Introductionmentioning
confidence: 91%
“…Using DNA fragments derivatized with the alkyne profluorophore and an azide at the 3' and 5' ends, respectively, the reaction proceeded in a sequence-specific templated fashion at template concentrations as low as 20 nm. [48] The use of excess tris(3-hydroxypropyltriazolylmethyl)amine ligand helped to prevent the copper-induced degradation of reac- tants, but also interfered with the fluorescence readout. Reliable results were obtained after thermal denaturation or copper removal with sodium sulfide.…”
Section: Azide-alkyne Cycloaddition (The Click Reaction)mentioning
confidence: 99%
“…Unter Verwendung von DNA‐Fragmenten, die mit dem Alkin‐Profluorophor und einem Azid an den 3′‐ bzw. 5′‐Enden derivatisiert waren, lief die Reaktion sequenzspezifisch in Templat‐gestützter Weise bei geringen Templatkonzentrationen von 20 n M ab 48. Ein Überschuss an Tris(3‐hydroxypropyltriazolylmethyl)amin‐Ligand half, den Kupfer‐induzierten Abbau der Reaktanten zu verhindern, störte jedoch die Fluoreszenzdetektion.…”
Section: Templat‐gestützte Strangligationunclassified